ANALISIS PENGARUH PENGETAHUAN TENTANG HIV, EFEKTIFITAS KONDOM DAN KEMUDAHAN MEMPEROLEH KONDOM TERHADAP PENGGUNAAN KONDOM DALAM PENCEGAHAN HIV - Lourensius L. T, Nerys (Universitas Negeri Yogyakarta, 2015)
The phenomenon of HIV (Human Immunodeficiensi Virus) and AIDS (Acquired Immunodeficiency Syndrome) has become a global issue. Various efforts have been and are being made to suppress the spread of HIV. HIV / AIDS has become a very serious epidemic threatening the health of the world community, through the United Nations decided to establish a separate body to deal with an epidemic of this one, namely UNAIDS. Meanwhile, since 1990, the World Population Agency (UNFPA), which had already been established also play an active role to combat the spread of HIV / AIDS, by running a comprehensive program in the field of reproductive health. The program is done either through the provision of information and education to the public and advocacy to mobilize political commitment and facilitate policies that support reproductive health.This study is a qualitative research using primary and secondary data. The primary data obtained through interviews, questionnaires by respondent Laki laki Seks Laki laki (LSL) that accessing condoms in NGOs VestaYogyakarta, while the secondary data obtained from the document. The survey results revealed that knowledge about HIV variables (X1) does not have a partial effect on the use of condoms in HIV prevention (Y) in LSL in NGO Vesta. Variable knowledge of the effectiveness of condoms have a partial effect on the use of condoms in HIV prevention (Y) in LSL in NGO Vesta. Variable ease of obtaining condoms (X3), does not have a partial effect on the use of condoms in HIV prevention (Y) in MSM in NGO Vesta.Variable knowledge of HIV (X1), knowledge of the effectiveness of condoms (X2) and the ease of obtaining condoms (X3) jointly influence simultaneously against the use of condoms in HIV prevention (Y) on Vesta NGO LSL in Yogyakarta. From the results of Adjusted R Square (because four variables) obtained yield was 0.392. In other words, 39.3% contribution variables influence of knowledge about HIV (X1), knowledge of the effectiveness of condoms (X2) and the ease of obtaining condoms (X3) on the dependent variable, namely the use of condoms in HIV prevention (Y).